Effect of diphosphonate on the prevention of X-radiation-induced inhibition of bone formation in rats - Ubios, Angela M.; Guglielmotti, M. B.; Cabrini, Rómulo Luis (John Wiley & Sons, Inc., 1986)
Fil: Ubios, Angela M. Comisión Nacional de Energía Atómica; Argentina